Implementasi Kebijakan Program E-Retribusi Pasar Daerah Kabupaten Blitar Tahun 2022-2024 - Kharisma Meidhi Aullia; Hery Basuki; Wydha Mustika Maharani (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
E-retribution in Blitar Regency replaces the manual method with electronic payment for market retribution. The use of the E-retribution system is still low, with only 10% of traders. This study aims to determine the policy implementation process, including communication, resources, disposition, and bureaucratic structure, as well as supporting and inhibiting factors based on Van Meter and Van Horn's theory. The research was conducted using a descriptive qualitative method, with primary data from interviews and observations, and secondary data from relevant documents. The results of this study show that the e-retribution policy has been implemented well, as evidenced by four factors: communication, resources, disposition, and bureaucratic structure being fulfilled. The supporting factors for the success of e-retribution are legal foundations and the insufficient revenue needs, while the inhibiting factors are inadequate infrastructure, lack of trader awareness, and outdated data on active traders in the market.